Internet Media During the COVID-19 Crisis - Trishchuk, Olga; Grytsenko, Oksana; Figol, Nadija; Faichuk, Tetiana; Teremko, Vasyl (Cuestiones Políticas, 2020)
This article defines the main characteristics of the media during quarantine, analyzes the peculiarity of online media during the crisis caused by the coronavirus pandemic COVID-19 and highlights changes in the content of media platforms during the spread of the coronavirus pandemic, considering changes in user interests and new media projects offered especially during this pandemic. General scientific research methods (analysis, synthesis) and special research methods of online media characteristics (content analysis) have been used. Based on the results of the survey, the most popular online platforms were identified during quarantine restrictions, the most vulnerable areas of online media were identified during the crisis, and details of the presentation of material on OVID-19 were analyzed by various means. It is concluded that social quarantine restrictions have led to an increase in activity among users of online media, now focusing on the content of the information and the constant monitoring of the situation of the pandemic, as well as ways to defend against it.